2015
DOI: 10.1039/c4cy01333f
|View full text |Cite
|
Sign up to set email alerts
|

Solar thermal catalytic reforming of natural gas: a review on chemistry, catalysis and system design

Abstract: Solar thermal catalytic reforming of natural gas is a promising route to increase the efficiency of fossil fuels utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 133 publications
(301 reference statements)
2
54
0
Order By: Relevance
“…The composition of natural gas is variable, but it is mostly composed of CH 4 (usually >90%), with the rest comprising CO 2 , small amounts of ethane, and negligible quantities of longer‐chained hydrocarbons and impurities. In the chemical industry, natural gas is converted to synthesis gas via the steam reforming process over Ni‐based catalysts . If hydrogen is a desired product rather than syngas (e.g., in ammonia synthesis), additional steps of water gas shift and separation are required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of natural gas is variable, but it is mostly composed of CH 4 (usually >90%), with the rest comprising CO 2 , small amounts of ethane, and negligible quantities of longer‐chained hydrocarbons and impurities. In the chemical industry, natural gas is converted to synthesis gas via the steam reforming process over Ni‐based catalysts . If hydrogen is a desired product rather than syngas (e.g., in ammonia synthesis), additional steps of water gas shift and separation are required.…”
Section: Introductionmentioning
confidence: 99%
“…Steam methane reforming (SMR) is a highly endothermic, reversible process with CH 4 conversion thermodynamically favored at high temperatures and low pressures . The overall SMR process is commonly described by three reactions: reforming to CO, water gas shift, and direct reforming to CO 2 , as shown in Eqs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Commercial parabolic trough collector (PTC)-based reactors have been operated under the sun for enhanced hydrogen production. [3,104] The type of materials used to construct the reactor is an important parameter;t hey should have high light transmittance and high thermals tability. [105] Recent studies have shown microreactors to be very effective for carrying out controlled reactions under light.…”
Section: Discussionmentioning
confidence: 99%
“…For such applications 50% conversion would be a very reasonable upgrade of the CH 4 heating value saving of ca. 10% of natural gas (as it can be easily calculated from heating values of corresponding gases) [39].…”
Section: Effect Of Temperature and Steam-to-carbon Ratiomentioning
confidence: 99%